Extreme polarization anisotropy in resonant third-harmonic generation from aligned carbon nanotube films - Zhu, Song (2023)
Carbon nanotubes (CNTs) possess extremely anisotropic electronic, thermal, and optical properties owing to their 1D character. While their linear optical properties have been extensively studied, nonlinear optical processes, such as harmonic generation for frequency conversion, remain largely unexplored in CNTs, particularly in macroscopic CNT assemblies. In this work, macroscopic films of aligned and type-separated (semiconducting and metallic) CNTs are synthesized and polarization-dependent third-harmonic generation (THG) from the films with fundamental wavelengths ranging from 1.5 to 2.5 µm is studied. Both films exhibited strongly wavelength-dependent, intense THG signals, enhanced through exciton resonances, and third-order nonlinear optical susceptibilities of 2.50 × 10-19  m2  V-2 (semiconducting CNTs) and 1.23 × 10-19  m2  V-2 (metallic CNTs), respectively are found, for 1.8 µm excitation. Further, through systematic polarization-dependent THG measurements, the values of all elements of the susceptibility tensor are determined, verifying the macroscopically 1D nature of the films. Finally, polarized THG imaging is performed to demonstrate the nonlinear anisotropy in the large-size CNT film with good alignment. These findings promise applications of aligned CNT films in mid-infrared frequency conversion, nonlinear optical switching, polarized pulsed lasers, polarized long-wave detection, and high-performance anisotropic nonlinear photonic devices.